Apology–forgiveness in restorative justice: Victims’ experiences with justice-involved youth - MacDiarmid, Laura (International review of victimology, 2025)
The exchange of apology and forgiveness in restorative justice is regarded as an important marker of symbolic reparation that is imbued with ritual significance. Despite this, how victims assess the sincerity of such remedial work has received limited empirical focus. It also remains unclear what role, if any, apologies play in precipitating victim forgiveness in restorative justice. The current study prioritizes victims’ experiences in Youth Justice Committees, a programme model of restorative justice in Canada, to explore the apology–forgiveness cycle. Analysis of data collected through 14 semi-structured interviews with victims who participated in 16 restorative justice programmes reveals that, for an apology to be deemed sincere, it requires the youth to accept responsibility for the harm, to express affect that conveys their recognition of the harm, and to take steps to make amends. In many instances, a sincere apology prompted forgiveness from the victim; however, the trajectory from apology to forgiveness was not always sequential. Results are discussed considering factors – such as the role of parents/guardians, age, and offence severity – that mediate the likelihood of apology and forgiveness in restorative justice programmes with justice-involved youth.